Pengaruh Model Pembelajaran Problem Based Learning terhadap Keterampilan Berpikir Kritis Siswa dalam Pembelajaran IPAS di Sekolah Dasar - Uliyana Nurkhotimah; Awalina Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Problem Based Learning (PBL) model on students’ critical thinking skills in the learning of Natural and Social Sciences (IPAS) in elementary school. The background of this research is the low level of students’ critical thinking skills, which was also identified through observations at SDN Pasirsari 01. The research method used is quantitative experimental with a Nonequivalent Control Group Design. The research population consists of all 70 fifth-grade students of SDN Pasirsari 01, divided into an experimental class (VA) and a control class (VB), each comprising 35 students. The sample was selected using a purposive sampling technique. Data were collected through test instruments in the form of pre-tests and post-tests. The results show that the implementation of the PBL model in the experimental class was carried out in the “Very Good” category (86.7%). There was a significant difference between the learning outcomes of students in the experimental class and the control class, as evidenced by the post-test average score of the experimental class being 79.27, much higher than the control class average score of only 37.83. Hypothesis testing using the t-test showed a significance value of 0.000 < 0.05, indicating that the PBL model had a significant effect on students’ critical thinking skills. Simple linear regression analysis further confirmed this finding, showing a contribution effect of 86.6%. Based on these findings, it can be concluded that the Problem Based Learning model has a positive and significant effect in improving the critical thinking skills of fifth-grade students in IPAS learning.